2012
DOI: 10.1371/journal.pone.0051664
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Bilirubin Clearance and Intestinal Interleukin-6 Expression in Bile Duct-Ligated Vitamin D Receptor Null Mice

Abstract: The vitamin D receptor (VDR) mediates the physiological and pharmacological actions of 1α,25-dihydroxyvitamin D3 in bone and calcium metabolism, cellular growth and differentiation, and immunity. VDR also responds to secondary bile acids and belongs to the NR1I subfamily of the nuclear receptor superfamily, which regulates expression of xenobiotic metabolism genes. When compared to knockout mouse investigations of the other NR1I nuclear receptors, pregnane X receptor and constitutive androstane receptor, an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 71 publications
(135 reference statements)
0
10
0
Order By: Relevance
“…We chose IL-6 because its level is higher after bile duct ligation and in patients with HCC and CCA. (28)(29)(30) We found that IL-6 (10 ng/mL) treatment of H69 cells for only 4 hours significantly reduced MAT1A and PHB1 mRNA levels by 22% and 26%, respectively, and raised c-MYC, MAFG, and c-MAF by 40%-53%. These results suggest that bile acids are not likely to be responsible for causing the changes in these genes but, rather, proinflammatory cytokines such as IL-6.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We chose IL-6 because its level is higher after bile duct ligation and in patients with HCC and CCA. (28)(29)(30) We found that IL-6 (10 ng/mL) treatment of H69 cells for only 4 hours significantly reduced MAT1A and PHB1 mRNA levels by 22% and 26%, respectively, and raised c-MYC, MAFG, and c-MAF by 40%-53%. These results suggest that bile acids are not likely to be responsible for causing the changes in these genes but, rather, proinflammatory cytokines such as IL-6.…”
Section: Discussionmentioning
confidence: 96%
“…Because this is unlikely to be relevant during bile duct ligation, we then explored the possibility that IL‐6 may be involved in triggering the observed changes in gene expression during bile duct ligation. We chose IL‐6 because its level is higher after bile duct ligation and in patients with HCC and CCA . We found that IL‐6 (10 ng/mL) treatment of H69 cells for only 4 hours significantly reduced MAT1A and PHB1 mRNA levels by 22% and 26%, respectively, and raised c‐MYC , MAFG , and c‐MAF by 40%‐53%.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, VDR governs the TGF-β/smad signal, thus playing an important role in modulating fibrosis (Ding et al, 2013;Beilfuss et al, 2015;Duran et al, 2016). In cholestasis, VDR can regulate the metabolism and transport of BA, and VDR deficiency promotes liver injury in mice (Ogura et al, 2009;Ishizawa et al, 2012;Firrincieli et al, 2013). Multiple recent studies highlight antiinflammatory effect of VDR which is very likely to serves as a potentially effective therapeutic strategy for liver diseases and urgently needs in-depth researched.…”
Section: Introductionmentioning
confidence: 99%
“…The VDR-null ( Vdr(−/−) ) mice and wild-type mice ( Vdr( +/+) ) mice were obtained by breeding Vdr(+/−) mice on a pure C57BL/6J background [ 52 ]. Original Vdr(−/−) mice were kindly provided by Shigeaki Kato and Chugai Pharmaceutical Co. [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The tissues were crushed using a Bessman Tissue Pulverizer (Spectrum Laboratories, Racho Dominguez, CA, USA), and the total RNA extraction was performed using the acid guanidium thiocyanate/phenol/chloroform method [ 52 ]. The cDNAs were synthesized using the ImProm-II Reverse Transcription system (Promega, Madison WI, USA), and the real time polymerase chain reaction was performed on the ABI PIRSM 7000 Sequence Detection System (Life Technologies Corporation, Carlsbad, CA, USA) using Power SYBR Green PCR Master Mix (Life Technologies Corporation) and primers reported previously [ 16 , 22 ].…”
Section: Methodsmentioning
confidence: 99%